SUSTAINABLE DEVELOPMENT IN MALAYSIA: THE WAY FORWARD AND CHALLENGES IN THE MODERN ERA - Basir, Salawati Mat (Brawijaya Law Journal, 2014)
ABSTRACTÂ The 1992 United Nations Conference on Environment and Development or â€œEarth Summitâ€ that was held in Rio de Janeiro, Brazil had established Agenda 21 which contain the blueprint for sustainability in the 21st century. Malaysia, in achieving the 21 Agenda had formulated initiatives and efforts to achieve the objective of sustainable development in all aspects, particularly social, economy and environment. This research analysed steps and efforts taken by government to achieve target of Vision 2020 to be a fully developed nation in terms of economy, social justice, political stability, quality of life and social values. Other than that, this research analysed the challenges and dilemma faced by Malaysia that can hinder Malaysia to achieve the sustainable development holistically and recommendations to overcome this challenges and dilemma.Â Â Keywords: Sustainable development, Malaysia, Agenda 21, challenges.Â Â Â